Comparing Knowledge-Based Sampling to Boosting - Martin Scholz (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2005)
Boosting algorithms for classification are based on altering the ini- tial distribution assumed to underly a given example set. The idea of knowledge-based sampling (KBS) is to sample out prior knowledge and previously discovered patterns to achieve that subsequently ap- plied data mining algorithms automatically focus on novel patterns without any need to adjust the base algorithm. This sampling strat- egy anticipates a user's expectation based on a set of constraints how to adjust the distribution. In the classified case KBS is similar to boosting. This article shows that a specific, very simple KBS algo- rithm is able to boost weak base classifiers. It discusses differences to AdaBoost.M1 and LogitBoost, and it compares performances of these algorithms empirically in terms of predictive accuracy, the area under the ROC curve measure, and squared error.
Keywords: 519